Republic of Azerbaijan : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Republic of Azerbaijan. (IMF Staff Country Reports; Country Report, 2008)
This Article IV Consultation reports on policies of the Republic of Azerbaijan. These policies contain inflation and measures to strengthen the resilience of the banking system to promote the development of the financial sector. Non-oil GDP continued to expand rapidly, pushed by large increases in public expenditure, including wages and pensions. The authorities intend to continue with their expansionary fiscal plans in 2008, in line with their strategy to pursue fast improvements in living standards and infrastructure to set the basis for long-term non-oil growth.